2021
DOI: 10.3390/foods10112762
|View full text |Cite
|
Sign up to set email alerts
|

Quality Formation of Adzuki Bean Baked: From Acrylamide to Volatiles under Microwave Heating and Drum Roasting

Abstract: Baked adzuki beans are rich in tantalizing odor and nutritional components, such as protein, dietary fiber, vitamin B, and minerals. To analyze the final quality of baked beans, the acrylamide and volatile formation of adzuki beans were investigated under the conditions of microwave baking and drum roasting. The results indicate that the acrylamide formation in baked adzuki beans obeys the exponential growth function during the baking process, where a rapid increase in acrylamide content occurs at a critical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The color changes were associated with Maillard reactions and caramelization during heating, and Krysiak et al [ 26 ] suggested the physical and chemical changes of the bean, depending on the temperature, as follows: (1) tissue destruction and structural changes, including protein denaturation at 50–60 °C; (2) non-enzymatic browning and water evaporation of bean seed over at 100 °C; (3) thermal decomposition into volatile compounds, as well as caramelization, oxidation, and esterification above 180 °C. Yao et al [ 27 ] suggested that the overall color of the adzuki beans showed a sharp decline, due to the thermal accumulation inside the baked beans resulting from microwave heating ( p < 0.05), which caused an obvious Maillard reaction in the adzuki beans in a short time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The color changes were associated with Maillard reactions and caramelization during heating, and Krysiak et al [ 26 ] suggested the physical and chemical changes of the bean, depending on the temperature, as follows: (1) tissue destruction and structural changes, including protein denaturation at 50–60 °C; (2) non-enzymatic browning and water evaporation of bean seed over at 100 °C; (3) thermal decomposition into volatile compounds, as well as caramelization, oxidation, and esterification above 180 °C. Yao et al [ 27 ] suggested that the overall color of the adzuki beans showed a sharp decline, due to the thermal accumulation inside the baked beans resulting from microwave heating ( p < 0.05), which caused an obvious Maillard reaction in the adzuki beans in a short time.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in TPC and TFC is thought to be due to the generation of aminocarbonyl reaction products, such as melanoidin, which have a high free radical scavenging ability because of heat generated by microwaves. Yao et al [ 27 ] reported that the heating process leads to precursors of volatile substances, and the thermal decomposition of oligosaccharides generates reducing sugars. Consequently, a reaction between the free amino acids and reducing sugars releases furans, pyrazines, etc.…”
Section: Resultsmentioning
confidence: 99%